Latent factor models for the Chinese commodity futures markets - Liu, Yanchu; Zhou, Heyang; Yang, Haisheng (Pacific-Basin finance journal, 2025)
The rapid growth of Chinese commodity futures markets over the past several decades has created a fertile ground for exploring underlying market dynamics. In this research, we utilize Instrumented Principal Component Analysis (IPCA) alongside the Conditional Autoencoder (CA) method to construct latent factor models tailored to this market. By uncovering hidden patterns and intrinsic characteristics that drive futures prices, our empirical results demonstrate robust out-of-sample predictive accuracy. •We develop IPCA and CA models for Chinese Commodity Futures Markets.•We expand the set of profitable factors available for Chinese Commodity Futures Markets.•Comprehensive explanations with insights for the uncovered factors are provided.